Sharia Compliance in Broiler Chicken Egg Trading Practices in Padakkalawa Village, Pinrang Regency - Ilham; Mahsyar; Budiman; Rustam Magun Pikahulan (Journal of Sharia Economic Law, 2026)
This study analyzes sharia compliance in the buying and selling of purebred chicken eggs in Padakkalawa Village, Mattiro Bulu District, Pinrang Regency. This study is motivated by the importance of purebred chicken eggs as a strategic food commodity and the potential for muamalah problems, such as unclear product quality, mixing good eggs with damaged eggs, tempo payments, and liability for defective goods. This research employs empirical legal methods, juridical-sociological approaches, and Islamic law. Data were obtained through observations, interviews with farmers, retailers, and consumers, and documentation of transaction practices. The results of the study show that the buying and selling of purebred chicken eggs takes place simply, based on trust, and follows the market price. The practices of egg sorting, price transparency, and replacement of damaged eggs demonstrate the value of sharia compliance. However, clarity of contract objects, transparency of quality, recording of tempo payments, and reimbursement mechanisms for all consumers still need to be strengthened. This research confirms that the transaction of purebred chicken eggs can be in accordance with Islamic law if it is carried out honestly, transparently, fairly, and free from gharar and tadlīs.